EL TLC PERU-ESTADOS UNIDOS: REINSERCIÓN ECONÓMICA INTERNACIONAL O SUBORDINACIÓN NACIONAL - Bouby Tolentino, Francisca (2006)
The Free Trade Agreement (FTA) between Peru and the United States of America has as objectives the consolidation and the enlargement of the temporary benefits established, for certain products, with the ATPA and the further ratification with the ATPDEA and also to intensify a structural adjustment policies. These issues set in question the functions of the State, in its role of leading the actions of coordination and promotion of the national productive forces, leading actions to overcome the existing barriers in order to reach productivity and competitve levels needed to face up the high competition that signifies a FTA with a developed economy as the USA and to achieve an active reinsertion in the global economy generating an endogenous growing. The alternative is to let be taken to the forces of attraction in a context of laissez-faire that would lead to a passive reinsertion generating bigger polarization among the members of the Peruvian society.